Effect of Temperature on the Thermal Stability and Staining Quality of Parijoto Fruit Extract as a Counterstain in Gram Staining - Indah Sari; Nurhayati Nurhayati; Siti Akhirunnisah Rusera; Putri Anggraini; Sukron Sukron; Simon Martin Manyanza Nzilibili (Journal of Health and Nutrition Research, 2026)
Gram staining is a differential staining procedure that distinguishes between Gram-positive and Gram-negative bacteria. Toxicity and health hazards arising from the use of safranin dye have been widely reported, especially the danger of dye contamination originating from synthetic dye waste. Safranin is one of the dyes in Gram staining. Anthocyanin is a natural pigment that has the potential to be used as a dye, including applications in the laboratory such as Gram staining. Parijoto is a red fruit and contains anthocyanin. To evaluate the stability of parijoto fruit extract as a contrast dye for Gram staining based on temperature variations. The research design used was a true experimental design. Samples were E. coli bacteria to see the results of microscopic examination using alternative parijoto fruit extracts and safranin as a control in Gram staining. Data were processed using descriptive analysis based on the results of Gram staining. All treatment groups showed clear background contrast, good color, optimally stained bacteria, and clean preparations without debris. The best results were obtained with safranin (100%), followed by parijoto extract without heating (85%), heating at 40°C (80%), and heating at 80°C (75%), with a tendency to decrease in quality as the temperature increases.  Parijoto fruit extract can be used as an alternative contrast dye in Gram staining, with the best results in conditions without heating, while increasing the temperature decreases the staining quality. Parijoto fruit extract has the potential to be an alternative natural contrast dye that is safer and more environmentally friendly. Use without heating is recommended because it provides optimal results and can be further developed in laboratory tests.